Water-level elevation governs iron-bound organic carbon dynamics in a reservoir drawdown zone - Haojun Deng; Zhuangpeng Zheng; Zhi Zhang; Aimin Chen; Guiling Lin (Journal of Soils and Sediments, 2026)

Environmental factors shape the intestinal microbiota and function of Manila clam Ruditapes philippinarum - Bifu Gan; Guiling Li; Yanru Xu; Jingmiao Yang; Weilang Lin; Xiaobo Yan; Maozi Lin; Guangmao Ding; Fang Su; Qizhen Xiao (Frontiers in Marine Science, 2026)
Intestinal microbiota of aquatic animals is closely associated with the environment, influencing their health, immune defense, and environmental adaptability. To understand the relationships among the Manila clam ( Ruditapes philippinarum ) intestinal microbiota, the bacterial communities in their habitats, and environmental factors, as well as the characteristics and potential functions of the intestinal microbiota. This study systematically analyzed the bacterial communities in the clam intestines, seawater, and sediment samples from two typical habitats using 16S rRNA gene (V3-V4) sequencing. The results revealed significant differences in bacterial community composition among the intestines, seawater and sediment, with pronounced regional variations also evident within the same sample type. The clams gut microbiota in Fuqing was predominantly composed of Alphaproteobacteria , Gammaproteobacteria , Bacteroidota , Bacillota , and Cyanobacteria . In Putian, Cyanobacteria comprised an exceptionally high proportion. However, Bacillota , Bacteroidota , and Actinomycetota showed similar relative abundances in both regions, indicating a potential “core bacterial community”. Regarding the α-diversity of gut microbiota, although no significant differences were observed between clam samples from the two regions, their diversity was significantly lower than that of the sediment bacterial communities. The intestinal bacterial communities exhibited high similarity to the aquatic bacterial communities in terms of richness, diversity, and dominant species abundance, and it shares most of the ASVs with the sediment, suggesting that environmental microorganisms may serve as the primary source of the clam intestinal microbiota. Environmental drivers of bacterial communities differed regionally. In Fuqing, bacterial communities were associated with temperature, DO, pH, and salinity, and exhibited broader niche widths; in Putian, they were mainly influenced by nutrients, showing narrower niches. Compared to bacterial networks in the environment, the interactions among members within the gut bacterial communities of clams display modularity, indicative of functional specialization. The composition and functions of the intestinal microbiota of clams vary significantly in different environments, which may be a manifestation of their ecological adaptability. The composition and function of clam intestinal microbiota varied with environment, reflecting their ecological adaptability. These findings provide a scientific theoretical basis for water quality regulation and disease prevention in aquatic animal farming operations.

Thermophilic-vermicomposting enhances nitrogen retention and reduces greenhouse gas emissions via microbial gene regulation - Guiling Zheng; Xiaoxia Hao; Binyan Hong; Dongmei Jiang; Hongxi Qian; Lin Bai (International Biodeterioration & Biodegradation, 2026)

Multiple-level fault controlled hydrothermal system in Huangshadong, Southeast China: Insights from coupled geophysical and geochemical investigations - Lu Liu; Xianan Qin; Zheng’an Wei; Min Zhang; Honglei Shi; Xiting Long; Wenjing Lin; Mingxiang Qiu; Guiling Wang; Shihua Qi; Fei Liu (Geothermics, 2026)

A SERS-active microneedle array for rapid and minimally invasive lactic acid detection - Xinyu Sun; Kequan Chen; Yang Wang; Zhiwei Zhang; Jinfeng Lin; Guiling Liu; Dianhuai Meng; Jian Dong; Yan Huang (Analytica Chimica Acta, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

3D porous carbon materials in situ-embedded with Fe3C/Fe nanoparticles as high-performance anode electrocatalysts of microbial fuel cells - Shaochuan Wang; Dongsheng Zhao; Zhenghui Qiu; Guiling Zhang; Cunguo Lin (Journal of Environmental Chemical Engineering, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Effects of light intensity and light duration on growth performance and ovarian development in red swamp crayfish Procambarus clarkii (Girard, 1852) - Long Wang; Meng Hu; Lin Cai; Yurui Wang; Tianyu Guan; Chuankun Zhu; Hui Wang; Guiling Wang; Jiale Li (Aquaculture International, 2025)

First record of the sap beetle Phenolia picta invading Eastern honey bee (Apis cerana) (Hymenoptera, Apidae) colonies - Lin Du; Wenbin Liu; Xiaoshun Chen; Jinge Licao; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

Hydrogeochemistry of geothermal water in Huangshadong and adjacent areas of Guangdong province: Implications for water-rock interaction - Lu Liu; Guiling Wang; Yalu Li; Zhengan Wei; Wenjing Lin; Xianan Qin; Min Zhang; Shihua Qi; Xiting Long (Geothermics, 2024)

Absorption and utilization of polysaccharides from Cordyceps militaris fruiting bodies and their protective effects against CCl4-induced acute liver injury in mice - Lin Lan; Jingxin Wang; Hao Luo; Min Cao; Nianhong Guo; Guiling Fan; Shengyu Wang; Zaixing Sun; QiaoLing He; Yufeng Li (Food Bioscience, 2024)

Heat source model for Enhanced Geothermal Systems (EGS) under different geological conditions in China - Wenjing Lin; Guiling Wang; Haonan Gan; Shengsheng Zhang; Zhen Zhao; Gaofan Yue; Xiting Long (Gondwana Research, 2023)

Whole transcriptome analysis of three leaf stages in two cultivars and one of their F1 hybrid of Camellia sinensis L. with differing EGCG content - Jinke Lin; Iain W. Wilson; Guoping Ge; Guiling Sun; Fuliang Xie; Yanfang Yang; Liangyu Wu; Baohong Zhang; Jianqiang Wu; Yue Zhang; Deyou Qiu (Tree Genetics & Genomes, 2017)

Quantifying the preferential flow by dye tracer in the North China Plain - Qinghua Wu; Chunlei Liu; Wenjing Lin; Meng Zhang; Guiling Wang; Fawang Zhang (Journal of Earth Science, 2015)

Identification of housekeeping genes suitable for gene expression analysis in the pearl mussel, Hyriopsis cumingii, during biomineralization - Zhiyi Bai; Jingyun Lin; Keyi Ma; Guiling Wang; Donghong Niu; Jiale Li (Molecular Genetics and Genomics, 2014)